2020
DOI: 10.1001/jamanetworkopen.2020.9993
|View full text |Cite
|
Sign up to set email alerts
|

Association of Major Food Sources of Fructose-Containing Sugars With Incident Metabolic Syndrome

Abstract: IMPORTANCE Sugar-sweetened beverages (SSBs) are associated with increased risk of metabolic syndrome (MetS). However, the role of other important food sources of fructose-containing sugars in the development of MetS remains unclear. OBJECTIVE To examine the association of major food sources of fructose-containing sugars with incident MetS. DATA SOURCES MEDLINE, Embase, and Cochrane Library were searched from database inception to March 24, 2020, in addition to manual searches of reference lists from included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 68 publications
4
67
0
6
Order By: Relevance
“… 1 These risk factors are waist circumference, blood pressure, high-density lipoprotein level, triglycerides level, and hyperglycemia. 2 MetS is a growing public health problem and concern. The prevalence of MetS has increased from 25.3% to 34.2% among US adults, 3 and the prevalence of metabolic syndrome was 33.9% among Chinese adults as of 2010.…”
Section: Introductionmentioning
confidence: 99%
“… 1 These risk factors are waist circumference, blood pressure, high-density lipoprotein level, triglycerides level, and hyperglycemia. 2 MetS is a growing public health problem and concern. The prevalence of MetS has increased from 25.3% to 34.2% among US adults, 3 and the prevalence of metabolic syndrome was 33.9% among Chinese adults as of 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Evidences from preclinical investigations as well as observational and interventional trials indicated that Western-type diet (WD) is a key driver of chronic, low-grade metabolic inflammation [37,38]. The consumption of calorie-rich foods: highly processed, ultra-processed (formulations of many ingredients), in addition to sugar sweetened beverages, fructose-containing sugars, trans fats and saturated fats, salt, and other food additives have been proven to influence inflammation and lead to chronic diseases [39][40][41][42][43]. In addition, WD and other popular diets have been shown to alter intestinal microbiome, which in turn helps shape integrated immune responses.…”
Section: Lifestyle Factors: Chronic Inflammation Axismentioning
confidence: 99%
“…It was recently reported that isocaloric substitution with glucose and fructose represents no major differences on plasma glucose, insulin or plasma triglycerides [ 75 ] with expected differences of both sugars regarding postprandial plasma glucose and insulin, given the low glycemic index of fructose [ 76 , 77 ]. In a systematic meta-analysis of prospective studies, the association between SSB intake with increased metabolic syndrome risk was not extended to other important sources of dietary fructose [ 78 ]. Additionally, excessive weight gain in children is promoted by SSBs, which seems to be induced by its high caloric content [ 79 , 80 ].…”
Section: Effects Of Fructose Omega-3 Fatty Acids and Vitamin E Onmentioning
confidence: 99%